Zymomonas mobilis immobilized on loofa sponge: levan and ethanol production in semi-continuous fermentation - Queiroz Santos, Vidiany Aparecida [UNESP]; Vega-Estrada, Jesus; Montes Horcasitas, Maria Del Carmen; Garcia-Cruz, Crispin Humberto [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2017)
Zymomonas mobilis is a promising microorganism in the biotechnological production of ethanol and levan due to its low biomass and high tolerance to ethanol concentrations. Ethanol and levan production by Z. mobilis CDBB-603 immobilized on loofa sponge using semi-continuous fermentation is evaluated. The first experiment, conducted with initial volume 50 mL and incubated for 24 hours, produced maximum ethanol and levan production, respectively 13.56 g L-1 and 23.94 g L-1, with 250 g L-1 sucrose and without agitation, at 30 degrees C. The second experiment was based on the best condition obtained in the first, using fermenter with production scale of 200 mL and by semi-continuous process. The second experiment also assessed immobilized biomass reuse during 10 days (240 hours) and produced higher ethanol (34.64 g L-1) and levan (26.40 g L-1) production rates than in the first experiment. Experiment 2 also verified that the microorganism remained viable and produced ethanol and levan until the last (10(th)) recycle day.
Keywords: Luffa cylindrical; attachment; exopolysaccharide; alcoholic fermentation